Improving on Nature: Making a Cyclic Heptapeptide Orally Bioavailable1. Issue 45 (12th September 2014) - Nielsen, Daniel S.; Hoang, Huy N.; Lohman, Rink‐Jan; Hill, Timothy A.; Lucke, Andrew J.; Craik, David J.; Edmonds, David J.; Griffith, David A.; Rotter, Charles J.; Ruggeri, Roger B.; Price, David A.; Liras, Spiros; et al.
Abstract The use of peptides in medicine is limited by low membrane permeability, metabolic instability, high clearance, and negligible oral bioavailability. The prediction of oral bioavailability of drugs relies on physicochemical properties that favor passive permeability and oxidative metabolic stability, but these may not be useful for peptides. Here we investigate effects of heterocyclic constraints, intramolecular hydrogen bonds, and side chains on the oral bioavailability of cyclic heptapeptides. NMR‐derived structures, amide H–D exchange rates, and temperature‐dependent chemical shifts showed that the combination of rigidification, stronger hydrogen bonds, and solvent shielding by branched side chains enhances the oral bioavailability of cyclic heptapeptides in rats without the need for N‐methylation.